Conference proceedings / 32nd Bled eConference Humanizing Technology for a Sustainable Society, June 16 - 19, 2019, Bled (University of Maribor Press, 2019)
Bled eConference, organized by University of Maribor, Faculty of Organizational Sciences, has been shaping electronic interactions since 1988. Bled eConference is the oldest, most traditional and well renowned conference in the field with more than 30 years of tradition. The theme of this year’s 32nd conference is dedicated to “Humanizing Technology for a Sustainable Society”. In 2018, European Commission emphasized that in the future, competitiveness will be dependent on the ability to move towards sustainability, resource-efficiency and the ability to exploit the advantages of digital technologies. In the context of digital society, implementation of digital technologies to achieve higher efficiency and competitive advantage is insufficient. Society calls for different economy models; more responsible, righteous and less exploitative. In this year’s conference, we address various aspects of these challenges and provide directions and guidelines for organizations to meet and overcome these challenges on their way towards successful digital transformation. Themes covered in the papers of these proceedings are focused on: digital transformation; business model innovation; blockchain and social media; big data, data science, and decision support systems; e-health, digital wellness and wellbeing; new applications and organizational models; and novel approaches and cases in education in digital economy.